De-aggregation of New National Seismic Hazard Maps for Indonesia - Achmad Fauzi, Abdul Wahab; Usama Juniansyah, Fauzi (2013)
The new Indonesia Seismic Hazard Maps for revising the previous map in SNI 03-1726-2002 was published in July 2010. These maps developed by Team for Revision of Seismic Hazard Maps of Indonesia were based on probabilistic approach for 2% probability of exceedance (PE) in 50 years and deterministic approach by using three-dimensional seismic source models and by considering latest geological and seismological data and fragility curve of buildings. Seismic sources were represented by subduction, fault, and background zones. The new maps were developed based on PSHA method. A principal advantage of the probabilistic method is combining all the possible earthquakes affecting the site. This paper presents deaggregation of Indonesia Seismic Hazard Map 2010. Deaggregation for peak ground acceleration, 0.2-sec and 1.0-sec pseudo spectral acceleration (SA) is performed for 2% PE in 50 years (2475 years mean return period). The maps of mean and modal of magnitude and distance presented here are intended to provide information about the distribution of probabilistic seismic sources and to provide suggestions for seismic sources to use in developing artificial ground motion.